Explicative Cases of Controversial Issues in Neurosurgery - Signorelli, Francesco (IntechOpen, 2012)
Neurosurgery is a rapidly developing field of medicine. Therefore, staying keeping track of the advancements in the field is paramount for trainees as well as fully trained neurosurgeons. This book, fully available online, is a part of our effort of improving availability of medical information for anyone who needs to keep up-to-date.